Epistemic injustice: Power and the ethics of knowing - Fricker, Miranda (Oxford University Press, 2007)
In this exploration of new territory between ethics and epistemology, Miranda Fricker argues that there is a distinctively epistemic type of injustice, in which someone is wronged specifically in their capacity as a knower. Justice is one of the oldest and most central themes in philosophy, but in order to reveal the ethical dimension of our epistemic practices the focus must shift to injustice. Fricker adjusts the philosophical lens so that we see through to the negative space that is epistemic injustice. The book explores two different types of epistemic injustice, each driven by a form of prejudice, and from this exploration comes a positive account of two corrective ethical-intellectual virtues. The characterization of these phenomena casts light on many issues, such as social power, prejudice, virtue, and the genealogy of knowledge, and it proposes a virtue epistemological account of testimony. In this ground-breaking book, the entanglements of reason and social power are traced in a new way, to reveal the different forms of epistemic injustice and their place in the broad pattern of social injustice."–Book cover. Justice is one of the oldest and most central themes of philosophy, but sometimes we would do well to focus instead on injustice. This book argues that there is a distinctively epistemic genus of injustice, in which someone is wronged specifically in their capacity as a knower
https://oxford-universitypressscholarship-com.proxy.bibliotheques.uqam.ca/view/10.1093/acprof:oso/9780198237907.001.0001/acprof-9780198237907
Keywords: EDI; approches et analyses; cours; cycles supérieurs; discipline; fem1000; fem9000; injustices herméneutiques; injustices testimoniales; injustices épistémiques; justice sociale; phi4336; premier cycle; ressource en ligne; sciences humaines; thématiques; épistémologie

Conceituando Empoderamento na Perspectiva Feminista - Sardenberg, Cecília M B (2006)
Transcription d’une communication au séminaire International : « Trilhas do empoderamento de mulheres », Salvador da Bahia, 5-10 juin 2006.
Keywords: amérique latine; amériques; anthropologie; approches et analyses; brésil; cours; cycles supérieurs; discipline; empowerment; fem7000; inégalités; justice sociale; militance; mouvements sociaux; patriarcat; pratiques féministes; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sofia; systèmes d'oppressions; thématiques; épistémologie

Standpoint theory, situated knowledge and the situated imagination - Stoetzler, Marcel; Yuval-Davis, Nira (Feminist Theory, 2002)
The aim of the article is to further assess and develop feminist standpoint theory by introducing the notion of the ‘situated imagination’ as constituting an important part of this theory as well as that of ‘situated knowledge’. The article argues that the faculty of the imagination constructs as well as transforms, challenges and supersedes both existing knowledge and social reality. However, like knowledge, it is crucial to theorize the imagination as situated, that is, as shaped and conditioned (although not determined) by social positioning.
Number: 3 https://journals-sagepub-com.proxy.bibliotheques.uqam.ca/doi/pdf/10.1177/146470002762492024
Keywords: approches et analyses; cours; discipline; fem1000; justice sociale; militance; mouvements sociaux; point de vue situé; premier cycle; ressource en ligne; sciences humaines; thématiques; théories féministes; épistémologie

Black feminist thought: Knowledge, consciousness, and the politics of empowerment - Hill Collins, Patricia (Routledge, 2000)
A revision of a hugely successful book; this is the 'bible' of contemporary black feminist thought and is widely cited and taught as a seminal text. Completely up-to-date with recent events, trends in popular culture, current events, and politics.
Première publication : 1990 Édition 10e anniversaire
Keywords: 1900-1999; EDI; afro-féminisme; amériques; approches et analyses; discipline; féminismes noirs; incontournable; intersectionnalité; justice sociale; militance; périodes historiques; racisme; ressource en ligne; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; épistémologie; états-unis

Questionnements féministes et méthodologie de la recherche - Ollivier, Michèle; Tremblay, Manon (L'Harmattan, 2000)
La recherche féministe repose-t-elle sur une éthique de la recherche qui lui est propre, Est-elle mieux servi par les méthodes qualitatives que quantitatives ? Comment arrive-t-elle à concilier engagement politique et effort d'élaboration d'un discours vrai sur le monde ? Cet ouvrage présente quelques éléments essentiels de la réflexion féministe actuelle sur la méthodologie de la recherche en sciences humaines et sociales.
Keywords: approches et analyses; canada; cours; cycles supérieurs; discipline; discours; fem1000; fem7000; har4600; justice sociale; méthodologie; point de vue situé; premier cycle; pédagogie; sciences humaines; sciences sociales; thématiques; épistémologie